Postal questionnaire survey: the use of sleeping with the head of the bed tilted upright for treatment of orthostatic hypotension in clinical practice. - CUNNINGHAM, CONAL; COAKLEY, DAVIS (My University, 2006)
Orthostatic hypotension (OH) is common and affects one in five community-living older persons [1]. The incidence is higher amongst older in-patients [2] and those attending a syncope clinic [3]. The treatment of OH is through increasing peripheral vascular resistance and/or intravascular volume. Existing treatments such as increased water intake, salt replacement [4] and medications may lead to hypertension, and older people tend to tolerate these interventions poorly [5]. Drinking 2–2.5 l of fluids daily may be effective in younger patients [6, 7] but may be undesirable in older patients who can be prone to urinary incontinence. Sleeping with the head of the bed elevated (SHU) is established as part of the treatment modality for OH [6, 8, 9]. The European Society of Cardiology guidelines [9] recommend raising the head of the bed on blocks to permit gravitational exposure during sleep, which results in chronic intravascular volume expansion. Mathias and Bannister [10] recommend SHU as first-line treatment for OH in patients with autonomic failure (AF). Our literature review suggests that SHU at 12° or greater confers some benefit in patients with OH. However, the studies were small with sample sizes of eight subjects or less with varying ages (23–66 years), and the majority of the patients had AF (Table 1). A number of those studies used a combination of SHU, fludrocortisone, and increased water and salt intake, so identifying the exact contribution from SHU is often not possible. The improvement in orthostatic blood pressure (BP) with SHU from the studies is summarised in Table
PUBLISHED
Keywords: Orthostatic hypotension